APAKAH APLIKASI GAMES KAHOOT DAPAT DIGUNAKAN SEBAGAI MEDIA ASSESSMENT FOR LEARNING? - Cahyani, Meita Dwi; Nurrahman, Arief; Hendrantya, Eka Adi; Owen, Meutia Sulistyowati (Universitas Tanjungpura, 2024)
The concept of assessment for learning is usually used to provide feedback, monitor progress, and determine students' future learning progress. The Kahoot games application is an online-based test platform that can be used as an assessment medium for learning. This research aims to evaluate the use of the Kahoot games application as an assessment medium for learning. This research is descriptive quantitative research. Purposive sampling technique was used to take a sample of 93 students. An evaluation questionnaire consisting of product quality instruments, usability instruments and effectiveness instruments was used to collect data. The instrument was tested for content validity through expert judgment using the Aiken V formula. Construct validity testing using Exploratory Factor Analysis (EFA) was also carried out to see the validity of the questionnaire instrument. The instrument reliability test was carried out by looking at the value of Cronbach Alpha. The results of the analysis show that the evaluation questionnaire instrument meets this validity with a value of 0.81-1.00. The construct validity results show the KMO and Bartlett test value is 0.675 and the reliability value is 0.857, which means the instrument is valid and reliable. The evaluation results show that the product quality of the Kahoot games application is stated at 85.36%, which means very good, the application usability level is stated at 87.73%, which means very good, and the application effectiveness level is stated at 90.53%, which means very good. With these excellent evaluation results, it can be concluded that the Kahoot games application can be used as an assessment medium for learning for students.